Prediction of the occurrence of leprosy reactions based on Bayesian networks - de Andrade Rodrigues, Rafael Saraiva; Heise, Eduardo Ferreira José; Hartmann, Luis Felipe; Rocha, Guilherme Eduardo; Olandoski, Marcia; de Araújo Stefani, Mariane Martins; Latini, Ana Carla Pereira; Soares, Cleverson Teixeira; Belone, Andrea; Rosa, Patrícia Sammarco; de Andrade Pontes, Maria Araci; de Sá Gonçalves, Heitor; et al. (Frontiers in Medicine, 2023)
Introduction Leprosy reactions (LR) are severe episodes of intense activation of the host inflammatory response of uncertain etiology, today the leading cause of permanent nerve damage in leprosy patients. Several genetic and non-genetic risk factors for LR have been described; however, there are limited attempts to combine this information to estimate the risk of a leprosy patient developing LR. Here we present an artificial intelligence (AI)-based system that can assess LR risk using clinical, demographic, and genetic data. Methods The study includes four datasets from different regions of Brazil, totalizing 1,450 leprosy patients followed prospectively for at least 2 years to assess the occurrence of LR. Data mining using WEKA software was performed following a two-step protocol to select the variables included in the AI system, based on Bayesian Networks, and developed using the NETICA software. Results Analysis of the complete database resulted in a system able to estimate LR risk with 82.7% accuracy, 79.3% sensitivity, and 86.2% specificity. When using only databases for which host genetic information associated with LR was included, the performance increased to 87.7% accuracy, 85.7% sensitivity, and 89.4% specificity. Conclusion We produced an easy-to-use, online, free-access system that identifies leprosy patients at risk of developing LR. Risk assessment of LR for individual patients may detect candidates for close monitoring, with a potentially positive impact on the prevention of permanent disabilities, the quality of life of the patients, and upon leprosy control programs.